The Impact Of Gendang Beleq Exstracurricular on Character Development Of Students At Sman 1 Terara, East Lombok - Oktaviona, Dwi; Mariasa, I Nengah (Solah, 2025)
Gendang Beleq extracurricular activity is a non-formal program organized by schools as an effort to foster students’ interests, develop their talents, and shape their character through the traditional musical art of Lombok. This activity not only focuses on musical training but also instills moral and social values. This study aims to analyze the relationship and impact of the Gendang Beleq extracurricular activity on character development among students at SMAN 1 Terara. The research uses a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. The research subjects consisted of the extracurricular coach, two vice principals, and three students who are members of the Gendang Beleq group. The theoretical framework of this study is based on Sukardi’s theory (2009), which emphasizes the importance of real-life practice in a supportive social environment for character formation, and Elizabeth B. Hurlock’s theory of character development (1990). The findings show that student involvement in this activity is closely related to the process of character formation. The resulting impacts include increased discipline, responsibility, self-confidence, social awareness, teamwork ability, as well as a growing sense of cultural pride and nationalism. Therefore, the Gendang Beleq extracurricular activity is proven to be an effective medium for character building through meaningful social learning experiences.